PERBANDINGAN HASIL TANGKAPAN BUBU PADA JENIS TERUMBU BUATAN BAN DAN BAMBU DI PERAIRAN DESA TOISAPU KECAMATAN BAGUALA AMBON - Alberth Ch. Nanlohy (Universitas Pattimura, 2019)
Information about material kinds of artificial reef which effective for marine organism habitat is rare. Based on this fenomena, It is important to conduct a study about bamboo and tire artificial reef. The objective of this study is to find out a catch comparison and species compotition of pot catch on bamboo and tire artificial reef. Alternatif a widely used materials are bamboo and tire with consideration easy to obtain and economis. The result of this study show that the total catch during the study was 170 fishes from 8 species dominated by Siganus javus, Seranidae sp and Carangidae sp. The total catch of the Tire artificial reef was 87 fishes including 48,19 % Siganus sp, 23,53% Seranidae sp and 10,06 % Lethrinidae sp where as Bamboo artificial reef was 83 fishes including 33,34 % Siganus sps,26,3% Seranidae sp and 14,26 % Carangidae sp . The result showed that catch of bamboo artificial reef was significantly difference from the catch of tire artificial reef where the catch of tire artificial reef was higher than that catch of bamboo artificial reef.